Preliminary Part - New Perspective: Journal of Business and Economics, (New Perspective: Journal of Business and Economics, 2025)
New Perspective: Journal of Business and Economics seeks to bridge the gap between the general business practice and financial press through standard academic journals of business and economics. It publishes articles and reviews highlighting the ongoing research on contemporary issues in the fields of business, economics and management and their impact on management practices.